2019
DOI: 10.1161/circep.118.007120
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Comparison of Electrocardiographic Imaging and Epicardial Contact Mapping in Structural Heart Disease

Abstract: Background: The accuracy of ECG imaging (ECGI) in structural heart disease remains uncertain. This study aimed to provide a detailed comparison of ECGI and contact-mapping system (CARTO) electrograms. Methods: Simultaneous epicardial mapping using CARTO (Biosense-Webster, CA) and ECGI (CardioInsight) in 8 patients was performed to compare electrogram morphology, activation time (AT), and repolarization time (RT). Agreement between AT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 35 publications
1
37
1
Order By: Relevance
“…They describe that 78% of the 240 compared epicardial electrograms had a difference between reconstructed and measured activation recovery intervals of less than 10 ms with the epicardial potential method. A study by Graham et al directly compares reconstructed epicardial repolarization patterns with CARTO electroanatomical maps in patients with structural heart disease, and found correlation of repolarization sequences of 0.55 and RMSE of 51 ms [13]. Although it is difficult to directly compare these studies with the current study, our study shows results that are equivalent or even superior to the results from the other studies.…”
Section: Previous Studiessupporting
confidence: 60%
“…They describe that 78% of the 240 compared epicardial electrograms had a difference between reconstructed and measured activation recovery intervals of less than 10 ms with the epicardial potential method. A study by Graham et al directly compares reconstructed epicardial repolarization patterns with CARTO electroanatomical maps in patients with structural heart disease, and found correlation of repolarization sequences of 0.55 and RMSE of 51 ms [13]. Although it is difficult to directly compare these studies with the current study, our study shows results that are equivalent or even superior to the results from the other studies.…”
Section: Previous Studiessupporting
confidence: 60%
“…AF is arguably the most difficult arrhythmia to map noninvasively. Validation work in the ventricle has shown a moderate correlation between ECGI predicted activation times and that on epicardial contact mapping 24‐26 . The accuracy may be further reduced in areas of low voltage and the system may have difficulty identifying lines of the block.…”
Section: Discussionmentioning
confidence: 99%
“…Validation work in the ventricle has shown a moderate correlation between ECGI predicted activation times and that on epicardial contact mapping. [24][25][26] The accuracy may be further reduced in areas of low voltage and the system may have difficulty identifying lines of the block. The atria are also anatomically complex and the atria cannot be separated at the septum.…”
Section: Baseline Drivers and The Response To Pvimentioning
confidence: 99%
“…The 12‐lead ECG has been the main diagnostic modality for that purpose, however given the anatomical complexity of outflow tract region, proposed ECG algorithms are often cumbersome and lack specificity 14–17 . Prior studies have shown that NIEAM can reliably identify chamber of origin for OTVAs and can prevent unnecessary access and mapping, therefore reducing overall procedure time 10–12,18,19 . These studies have relied on general patterns of activation and while they provide insight on the chamber that is activated first, they cannot predict the exact SOO.…”
Section: Discussionmentioning
confidence: 99%